Cost-Effectiveness between Double and Single Fecal Immunochemical Test(s) in a Mass Colorectal Cancer Screening. (7th April 2016) - Cai, Shan-Rong; Zhu, Hong-Hong; Huang, Yan-Qin; Li, Qi-Long; Ma, Xin-Yuan; Zhang, Su-Zhan; Zheng, Shu
Abstract : This study investigated the cost-effectiveness between double and single Fecal Immunochemical Test(s) (FIT) in a mass CRC screening. A two-stage sequential screening was conducted. FIT was used as a primary screening test and recommended twice by an interval of one week at the first screening stage. We defined the first-time FIT as FIT1 and the second-time FIT as FIT2. If either FIT1 or FIT2 was positive (+), then a colonoscopy was recommended at the second stage. Costs were recorded and analyzed. A total of 24, 419 participants completed either FIT1 or FIT2. The detection rate of advanced neoplasm was 19.2% among both FIT1+ and FIT2+, especially high among men with age ≥55 (27.4%). About 15.4% CRC, 18.9% advanced neoplasm, and 29.9% adenoma missed by FIT1 were detected by FIT2 alone. Average cost was $2, 935 for double FITs and $2, 121 for FIT1 to detect each CRC and $901 for double FITs and $680 for FIT1 to detect each advanced neoplasm. Double FITs are overall more cost-effective, having significantly higher positive and detection rates with an acceptable higher cost, than single FIT. Double FITs should be encouraged for the first screening in a mass CRC screening, especially in economically and medically underserved populations/areas/countries.